Double Jeopardy: Prematurity and Congenital Heart Disease—What's Known and Why It's Important. Issue 1 (January 2022) - Costello, John M.; Kim, Faith; Polin, Richard; Krishnamurthy, Ganga
This article is based on a composite of talks presented during the Double Jeopardy: Prematurity and Congenital Heart Disease Plenary Session at NeoHeart 2020, a global virtual conference. Prematurity and low weight remain significant risk factors for mortality after neonatal cardiac surgery despite a steady increase in survival. Newer and lower weight thresholds for operability are constantly generated as surgeons gather proficiency, technical mastery, and experience in performing complex procedures on extremely small infants. The relationship between birth weight and survival after cardiac surgery is nonlinear with 2 kilograms (kg) being an inflection point below which marked decline in survival occurs. The prevalence of congenital heart disease (CHD) in premature infants is more than twice that in term born infants. Increased risk of preterm birth in infants with CHD is most commonly due to spontaneous preterm birth and remains poorly understood. Advances in Neonatal-Perinatal medicine have led to a marked improvement in survival of neonates born prematurely over the last several decades. However, the risk of severe morbidities including retinopathy of prematurity, intraventricular hemorrhage, bronchopulmonary dysplasia and necrotizing enterocolitis remains significant in extremely low birth weight infants. Premature infants with CHD are at a greater risk of prematurity related morbidities than premature infants without CHD. Interventions that have been successful in decreasing the risk of these morbidities are addressed.